Open knowledge and critical academic literacy - Farias, Miguel (Árboles y Rizomas, 2024)
The editor shares some reflections on the role of academic journals in the context of the Open Science project, comments on their implications for the processes of reading scientific texts and proposes that critical academic literacy should be part of open knowledge projects. He then presents the contents of the current issue.
Keywords: knowledge systems; critical academic literacy; open science